Organizational Culture Transformation in Church : The Role of Friendly Leadership Mediation in Shifting Performative Spirituality towards Oikos Theology - Susi Cicilya Surati (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
This study analyzes the mediating role of Friendly Leadership in transforming church culture from Performative Spirituality to Oikos Theology. Performative spirituality, which measures self-worth through performance and ritual, creates a hierarchical and oppressive church environment. This crisis demands a theological shift towards Oikos, a vision of the church as God's holistic, relational household that is responsible for the community and the environment. Through qualitative literature study methods, it was found that Friendly Leadership is a key mediator. This model, based on Christ's hospitality and friendship (John 15:15), serves a dual purpose: First, it dismantles performative spirituality by building psychological safety, reducing fear, and encouraging authentic vulnerability. Second, it effectively builds an Oikos culture by encouraging congregational participation (ownership) and expanding the church's focus from internal affairs to socio-ecological concerns. In conclusion, Friendly Leadership is a vital practical bridge for realizing healthy and inclusive cultural transformation for the 21st-century church.